NUTRITIONAL STATUS AND EATING BEHAVIOR AMONG ADOLESCENT GIRLS IN DAV PUBLIC SCHOOL, BERHAMPUR, GANJAM DISTRICT,ODISHA - Anita Pandey1* and Rojina Swayamsiddha Sahu2 (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
This cross-sectional study examines the eating habits and nutritional health status of 65 adolescence girls who study in DAV Public School, Berhampur, Odisha. Adolescence periodis very crucial for both physical and cognitive development, it is essential to comprehend the eating patterns and nutritional condition of this group. To provide targeted interventions for encouraging healthier lifestyles, the study uses a mixed-methods approach that combines anthropometric measurements, dietary assessments, and surveys to thoroughly evaluate participants' eating behaviours, nutritional status, and the impact of social media on adolescent girls' food preferences. It was found that the majority of the respondents were overweight and that social media had a significant impact on their dietary preferences and way of life. These results highlight the critical need for focused health treatments and educational initiatives that encourage healthier lifestyles among teenage girls. These efforts will eventually play a pivotal role in supporting the best possible growth, development, and well-being during adolescence and beyond.